Mapping Trachoma in Kaduna State, Nigeria: Results of 23 Local Government Area-Level, Population-Based Prevalence Surveys. (7th December 2016) - Muhammad, Nasiru; Mpyet, Caleb; Adamu, Mohammed Dantani; William, Adamani; Umar, Murtala Muhammad; Goyol, Musa; Muazu, Habila; Onyebuchi, Uwaezuoke; Isiyaku, Sunday; Flueckiger, Rebecca M.; Chu, Brian K.; Willis, Rebecca; et al.
ABSTRACT: Introduction : To prepare for global elimination of trachoma by 2020, the World Health Organization (WHO) recommends mapping of trachoma at district-level to enable planning of elimination activities in affected populations. The aim of our study was to provide data on trachoma for each local government area (LGA) of Kaduna State, Nigeria, as such data were previously unavailable. Method : As part of the Global Trachoma Mapping Project (GTMP), a population-based cross-sectional trachoma survey was conducted in each of the 23 LGAs of Kaduna State, between May and June 2013. The protocols of the GTMP were used. Results : The prevalence of trachomatous inflammation – follicular (TF) in children aged 1–9 years was between 0.03% and 8% across the LGAs, with only one LGA (Igabi) having a TF prevalence ≥5%. The LGA-level prevalences of trichiasis in persons aged 15 years and older were between 0.00% and 0.78%. Eleven LGAs had trichiasis prevalences of 0.2% and over in adults; a threshold equivalent to 1 case per 1000 total population. The LGA-level proportion of households with access to improved water sources ranged from 9% to 96%, while household access to latrines ranged from 5% to 99%. Conclusion : Kaduna State has generally hypoendemic trachoma, but a few trichiasis surgeries are still required to attain the WHO elimination targets. Better access to improved water and sanitation is needed.